Please find the sum of these problems with the steps:

1. (3x^5-2x^4+6x) and (2x^5+9x^4+4x)

2. (7x^2+9x^4+4-6x^3)-(8-4x^3+4x^4+5x^2)

Printable View

- Apr 16th 2007, 02:27 AMeliciaFind the sum of polynomials
Please find the sum of these problems with the steps:

1. (3x^5-2x^4+6x) and (2x^5+9x^4+4x)

2. (7x^2+9x^4+4-6x^3)-(8-4x^3+4x^4+5x^2) - Apr 16th 2007, 03:38 AMJhevon
Sum just means to add.

(3x^5-2x^4+6x) + (2x^5+9x^4+4x) ............expand the brackets

= 3x^5-2x^4+6x + 2x^5+9x^4+4x ..............now group like terms

= 3x^5 + 2x^5 - 2x^4 + 9x^4 + 6x + 4x ......now add the like terms

= 5x^5 + 7x^4 + 10x

Quote:

2. (7x^2+9x^4+4-6x^3)-(8-4x^3+4x^4+5x^2)

= 7x^2 + 9x^4 +4 -6x^3 - 8 + 4x^3 - 4x^4 - 5x^2 ...now group like terms

= 9x^4 - 4x^4 - 6x^3 + 4x^3 + 7x^2 - 5x^2 + 4 - 8 ..now add like terms

= 5x^4 - 2x^3 + 2x^2 - 4